Influence of pH and the C/N ratio on the biogas production of wastewater - A. Cerón-Vivas; K. T. Cáceres; A. Rincón; Á. A. Cajigas (Revista Facultad de Ingeniería Universidad de Antioquia, 2019)
Wastewater from institutions are considered with low strength and they may have a low C/N ratio and pH values higher than 7.0 units. In developing countries, anaerobic treatment for low strength wastewater is widely applied. However, COD removals and biogas production can be low due to inhibitions in the process. To improve the effluent quality, aerobic posttreatment has been used. The aim of this study was accessing the influence of pH and C/N ratio on methane yield of institutional wastewater, taking into account the aerobic sludge recirculation towards the anaerobic reactor. A factorial design 32 was used, evaluating different pH values: 6.9±0.1, 7.5±0.05 and 9.0±0.5; and C/N ratio: 4.9±0.2, 8.2±0.18 and 14.2±0.17. Biochemical methane (BMP) tests were performed using as inoculum a sludge with the hydrolytic, acidogenic and specific methanogenic activity of 2.79 gCOD/gVSS-d, 2.80 gCOD/gVSS-d and 0.14 gCODCH4/gVSS-d, respectively. Results indicating that with high C/N ratio, the methane yield increased. The maximum BMP was 318 L CH4/kgVSS with pH 7.5 and C/N ratio of 8.2±0.18; however, with the C/N ratio of 14.2±017 a major COD removal and methane production rate were observed.